PENGARUH PENGELUARAN, PMDN DAN INFLASI TERHADAP PENERIMAAN DI SUMATERA UTARA TAHUN 2001-2020 - Desember Palito Sinaga; Ali Asdon Tanjung; Feryanto Nababan; Mentari syaputri Purba; Raymond Siboro; Joko Suharianto (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the effects of domestic investments, inflasi, and pengeluaran on Sumatra Utara's income between 2001 and 2020. This study uses the Error Correction Model (ECM) analysis method to determine the impact of independent variables on dependent variables in the pendek data and the Regression Linear Berganda analysis to determine the impact of independent variables on dependent variables in the panjang data. According to the results of the ECM analysis, the variable pengeluaran in the panjang has a significant and positive impact on the sumatera utara's income, while the variable PMDN in the panjang has a positive but not significant effect, and inflasi has a negative and not significant effect. Conversely, the pendek jangka indicates that the pengeluaran variable also has a significant and positive impact on the Sumatera Utara's income, whereas the PMDN and Inflasi variables do not have a significant impact.